Attitudes of Physicians and Nurses Toward Interprofessional Collaboration: a Systematic Literature Review - Gregoriou, Polyxeni; Charalambous, Andreas; Rousou, Elena; Papastavrou, Evridiki; Merkouris, Anastasios (My University, 2025)
Interprofessional collaboration involves coordinated efforts by professionals from various disciplines, such as physicians and nurses, aimed at improving patient care outcomes. This teamwork enhances cooperation among healthcare professionals with diverse expertise, contributing significantly to patient safety, satisfaction, expedited recovery, cost-effectiveness, and reduced mortality rates.
Keywords: physicians; Interprofessional collaboration; attitudes; nurses